(untitled) (Jurnal Teknologi (Sciences & Engineering), 2017)
The main purpose of this article is to present the fluid dynamic and combustion performances of a can combustor applying double radial flow swirler. Analysis was conducted using Computational Fluid Dynamics simulation (CFD) and compared with experimental works conducted by previous researchers. Air pollution, in the form of gaseous emissions from gas turbine generator reportedly increasing every year. Design modifications was identified and used in this study where air swirler been proven able to reduce the formation rate of gaseous emission such as NOx and CO during combustion. Â Swirler in a burner is a device that serves to improve the air and fuel mixture in the main combustion zone. Swirlers, presently studied are from a combination of two radial swirlers with different vane angle (primary and secondary) such as 30o/40o, 30o/50o and 30o/60o. Â Application of Ansys Fluent 14 CFD solvers was used in this study. Turbulent flow model used was from Reynolds Average Navier-Stokes (RANS) type involving k-Ïµ. The fuel used is diesel. The parameters studied were wall temperature distribution along the combustor, the volume of NOx and volume of CO in the main combustion zone. Results from this study showed that the combination of 30o/60o generates the lowest gaseous emissions production rate. The highest average percentage error obtained by simulation studies compared to the actual experimental values for NOx was 22% and CO was 17.8%. Comparison between simulation and actual study proves that the simulation method can be used for preliminary decision and able to be used as benchmark to determine which is the best swirler configuration.